The impact of role models on women's self-selection in competitive environments - Kristina Meier; Alexandra Niessen-Ruenzi; Stefan Ruenzi (ZBW - Leibniz-Informationszentrum Wirtschaft, 2018)
We show that female role models increase women's willingness to compete. As in Niederle and Vesterlund (2007), we find that women are less willing to enter a tournament than men, although there are no gender differences in performance. However, the gender gap in tournament entry disappears if subjects are exposed to a competitive female role model. Results are stronger for the best performing women who seem to be particularly encouraged by female role models. Female role models also mitigate gender stereotype threats and lead to higher self-confidence among women. By contrast, we find that competitive male role models seem to intimidate female subjects and increase the gender gap in tournament entry even further. Our results have implications for the socio-political debate on how the fraction of women in top management positions can be increased.
Keywords: J16; C9; 330; Gender; Competition; Role Models